2017
DOI: 10.1186/s12974-017-1034-z
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors P2Y12R and P2X7R: potential targets for PET imaging of microglia phenotypes in multiple sclerosis

Abstract: BackgroundMicroglia are major players in the pathogenesis of multiple sclerosis (MS) and may play a dual role in disease progression. The activation status of microglia in vivo is highly dynamic and occurs as a continuum, with the pro-inflammatory and anti-inflammatory phenotypes on either end of this spectrum. Little is known about in vivo dynamics of microglia phenotypes in MS due to the lack of diagnostic tools. Positron emission tomography (PET) imaging is a powerful non-invasive technique that allows real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 35 publications
5
112
0
Order By: Relevance
“…In recent years, a few PET tracer candidates to image P2X7 receptors have been proposed [62], and some were evaluated in preclinical models of neuroinflammation [47,63,64]. For example, [ 11 C]GSK1482160 showed increased tracer uptake in both systemic LPS (5 mg/kg) model in mice [47] and in rats with experimental autoimmune encephalomyelitis (EAE) [63].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a few PET tracer candidates to image P2X7 receptors have been proposed [62], and some were evaluated in preclinical models of neuroinflammation [47,63,64]. For example, [ 11 C]GSK1482160 showed increased tracer uptake in both systemic LPS (5 mg/kg) model in mice [47] and in rats with experimental autoimmune encephalomyelitis (EAE) [63].…”
Section: Discussionmentioning
confidence: 99%
“…Although in general results have been positive, the use of TSPO as a marker for neuroinflammation has some limitations, such as an intracellular binding site, genetic polymorphisms, and additional binding sites on monocytes and vascular wall endothelium [6,7]. In addition, TSPO does not differentiate between resting state and pro-inflammatory and neuro-protective microglia subtypes [8]. Therefore, new PET tracers are needed, which specifically target proteins that reflect the status of microglial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new PET tracers are needed, which specifically target proteins that reflect the status of microglial cells. Recently, using wellcharacterised post-mortem tissues of patients with MS and activated human microglia, it has been demonstrated that the purinergic P2X 7 receptor is highly expressed on proinflammatory microglia and macrophages, is selectively expressed within MS lesions, and may be involved in the neuroinflammatory cascade [8][9][10]. To a lesser extent, expression of P2X 7 receptor has also been found in grey matter on astrocytes, oligodendrocytes, and neurons [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several radiolabeled P2X7 ligands have been developed and evaluated. Neither 11 C-A740003 (14) nor 18 F-EFB (15) showed appreciable brain uptake; however, 3 H-A740003 succeeded in recognizing the site of inflammation in human postmortem brain sections, as well as rodent brain sections when examined by in vitro autoradiography (16). 11 C-GSK1482160 (17) showed great promise due to its strong P2X7 selectivity, efficient radiosynthesis, and blood-brain barrier permeability.…”
mentioning
confidence: 99%